Electromyographic stages of denervation/reinnervation process in neuromuscular diseases: need for revision - S. S. Nikitin (Нервно-мышечные болезни, 2015)
Analysis of motor unit potentials (MUPs) parameters registered by needle EMG electrodes is the key for understanding changes of the motor units in different neuromuscular disorders. The classification of MUPs changes known as electromyographic stages (EMGS) of the denervation/reinnervation process (DRP) is based on the analysis of myogenic, synaptic neurogenic and neuronal disorders. Current article focuses on pathogenesis of typical and atypical MUPs of low duration, decreased and increased amplitude, additionally muscle biopsy data and neurophysiological assessment of muscle fiber density, and мacro-EMG. The absence of primary neurogenic disturbances in inflammatory and non-inflammatory muscle diseases, as well as in neuro-muscular junction disorders, confirmed by single fiber EMG and мacro-EMG makes it impossible to discuss the concept of EMG stages in patients with these levels of pathology. The EMG stages concept can be applied for peripheral nerve and motor neuron disturbances only, reflecting the volume but not the efficiency of reinnervation.